Analisis Kinerja Keuangan Sebelum dan Sesudah IPO di Daftar Efek Syariah - Adinda Umul Fadzila; Ria Anisatus Sholihah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The number of companies listed on the Sharia Securities List (DES) continues to grow, including those conducting Initial Public Offerings (IPOs). In 2021, 54 companies officially conducted IPOs, an increase from the previous year. IPO is one of the strategies to obtain additional capital and can have an impact on financial performance. This study aims to analyze the differences in financial performance before and after IPO in companies listed on DES in 2021. This study provides an overview of the company's financial condition before and after the IPO. This quantitative research uses secondary data from financial statements two years before and after the IPO. Using purposive sampling, 36 companies that met the criteria were selected. Wilcoxon test in SPSS was applied to assess the difference in financial ratios. The results show significant differences in financial ratios represented by CR, DER, and TATO before and after IPO. However, ROA did not show a significant difference. In addition, there is an average increase in the CR ratio, while the other ratios namely DER, ROA, and TATO show a decrease in average between before and after the IPO.